Effect of Thyroxine Hormone (T4) Addition in Feed to the Growth Rate Epinephelus fuscoguttatus - Mahyuddin Salim; Iskandar Putra; Rusliadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted from February 2016 to March 2016 at Batam Mariculture Development Center .The aim of this research was to investigate the dose of Thyroxine (T4) hormone in fish meal on the growth of fish Epinephelus fuscoguttatus. The research method used was experimental method and Complete Random Device (CRD) with four treatments and three replications. The treatments in this study were control (without thyroxine hormone), 0,3 mg Thyroxine hormone/kg of feed, 0,6 mg Thyroxine hormone/kg of feed and 0,9 mg Thyroxine hormone / kg of feed. The best result was treatment on 0,6 mg Thyroxine hormone/kg of feed with absolute growth weights (17,60 g), absolute growth length (1,75 cm), specific growth rate (1,30 %) and survival rate (100 %).Key word :Thyroxine (T4), Enlargement, Epinephelus fuscoguttatus